2017
DOI: 10.47604/ijfa.457
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Sensitivity to Market Risk on Internal Factors Affecting Financial Performance of Savings and Credit Societies in Kenya

Abstract: Purpose: The purpose of this study was to establish the moderating effect of sensitivity to market risk on internal factors affecting financial performance of savings and credit societies in Kenya. Methodology: The study employed an explanatory research design. The target population was 83 registered deposit taking SACCO’s in Kenya that have been in operation for the last five years. The sample size for the study was all 83 SACCOs that have remained in existence since 2011-2015. Census methodology was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
3
1
0
Order By: Relevance
“…The average mean for responses of financial performance was 4.27 implying that majority of the respondents agreed eith the statements on financial performance. The findings agree with the study carried by Barus (2018) on the influence of internal factors on the financial performance of deposit taking savings and credit societies in Kenya which concluded that profitability is an effective measure of financial performance of a firm.…”
Section: Financial Performance Of Epz Firmssupporting
confidence: 90%
See 3 more Smart Citations
“…The average mean for responses of financial performance was 4.27 implying that majority of the respondents agreed eith the statements on financial performance. The findings agree with the study carried by Barus (2018) on the influence of internal factors on the financial performance of deposit taking savings and credit societies in Kenya which concluded that profitability is an effective measure of financial performance of a firm.…”
Section: Financial Performance Of Epz Firmssupporting
confidence: 90%
“…An increase in EPZ firms asset quality means that the firms can easily access funds from the financial institutions. The results agree with Barus (2018) carried out a research on the effects of internal factors on the financial performance of deposit taking savings and credit societies in Kenya and established that asset quality affect financial performance of deposit taking savings and credit societies in Kenya.…”
Section: Multiple Regression Coefficientssupporting
confidence: 87%
See 2 more Smart Citations